Diversification of Molinia‐dominated blanket bogs using Sphagnum propagules. Issue 4 (9th December 2021) - Pilkington, Mike; Walker, Jonathan; Fry, Chris; Eades, Phil; Meade, Roger; Pollett, Nicholas; Rogers, Tony; Helliwell, Tom; Chandler, David; Fawcett, Emma; Keatley, Tom
Abstract: Increasing dominance by purple moor grass, Molinia caerulea (' Molinia ') on globally rare and protected blanket bogs of the United Kingdom and the South Pennines is a growing threat to diversity and carbon storage, as well as increasing the risk of wildfire. In a trial to increase diversity using Sphagnum plugs planted on three Molinia ‐dominated sites in the South Pennines, an initial rapid increase in cover of plug‐derived Sphagnum (PDS) suggested an advantage over that of naturally occurring Sphagnum colonies, the latter remaining below 1% cover throughout; subsequent plateauing of PDS cover in areas of moderate Molinia cover (<80%) was linked with drought stress, whereas declining cover in Molinia ‐dense areas (>80%) suggested additional competition for light. The cover of Molinia was only weakly reduced by, and then completely recovered from, a baseline flailing treatment. Increasing cover of PDS in all of the treatments had no clear effect on the cover of Molinia . The cover of naturally occurring indicator species was strongly reduced by the baseline flailing treatment; subsequent recovery was not complete, even with contributions by PDS. There was a negative linear relationship between Molinia cover and indicator species cover, over all ranges of Molinia cover. Water table depths were lowered by PDS during the first 3 years of the trial, perhaps due to facilitated capillary conduction of water through the buried plug tissues. It was concluded that PDS can establish rapidly amongst Molinia, boosting the diversity and cover of indicator species, but that establishment is slower in areas of dense Molinia and also likely to be hampered by periods of severe drought stress. Prior flailing had no clear benefit on the growth of PDS but reduced the cover of naturally occurring indicator species. Further investigations should include the role of water stress, shading and phosphorus limitation in restricting the growth of PDS within Molinia ‐dominated swards. Abstract : Areas of UK upland blanket bog are becoming increasingly dominated by purple moor grass, Molinia caerulea (' Molinia '), and this domination has been shown to reduce the diversity and abundance of other key blanket bog species with associated threats to carbon uptake and storage along with other ecosystem functions. This study provides a brief introduction to Molinia domination of upland blanket bogs in the United Kingdom and also reports on a trial initiated by Natural England in 2014 and carried out by Moors for the Future Partnership on three sites in the South Pennines. The results show highly successful and rapid initial growth of propagated Sphagnum colonies with a high diversity of Sphagnum species, but there was slower growth in the Molinia ‐dense areas of the gullies and over all areas of one of the sites. The study concludes that the use of Sphagnum plugs to diversify Molinia ‐dominated blanket bog be further investigated and makes recommendations for innovative treatments to promote plug‐derived Sphagnum growth.